Escritura (s). Borde (s). Arte (s) - Rodríguez, Claudia María del Valle; Galante, María Luz; Piretro, Ana Paula; Matarozzo, Ornella; Myszkoroski, Ivana (diseño); Bertea, Federico (ilustraciones) (Facultad de Artes, UNC, 2021)
Fil: Rodríguez, Claudia María del Valle. Universidad Nacional de Córdoba. Facultad de Artes; Argentina.